Films of endearment : a mother, a son and the '80s films that defined us - Koresky, Michael, 1979- (Hanover Square Press, 2021)
A successful film critic reflects on his dynamic mother and the '80s movies they shared together, in a meditation on loss and resilience and a celebration of the special bond between mothers and their sons.